[Aerial spraying] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Aerial spraying of the sugar cane crops at the Caroni Estate.
Cataloger's title
Keywords: Spraying and dusting in agriculture -- Trinidad and Tobago; Sugar crops -- Trinidad and Tobago; Caroni (1975) Limited